THE INFLUENCE OF IRON CONCENTRATION ON THE MECHANICAL PROPERTIES OF A356 AL ALLOY FOR CAR RIMS APPLICATION - Risonarta, Victor Yuardi; Anggono, Juliana; Aditya, Geraldi Raka (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
A356.0 aluminum-silicon alloy is a base material for car rims application. Car rims are critical components for a vehicle as they carry the load of the passengers, goods, and the weight of the vehicle itself, therefore they should be sufficiently strong to withstand the vertical load, fatigue load, impact load, the side load and the braking force. Car rims are made by gravity die casting process. During the casting process, the inclusion of iron-content parts entering the molten Al can take place which leads to higher iron (Fe) concentration. High Fe con concentration lowers the toughness and the ductility of car rims. This study investigates the maximum value of Fe concentration that can be tolerated for acceptable mechanical properties of Al-Si alloy A356.0 for car rims application. The Fe concentration studied was 0.12 %wt, 0.16 %wt, and 0.20 %wt. Evaluation was performed on tensile and impact properties of the specimens. The test results show that increased Fe concentration decreases elongation, yield strength and ultimate tensile strength (UTS). Furthermore, there is a quite large decrease in UTS (by 34 MPa) when Fe concentration increases only by 0.06 %wt. Impact strength decreases significantly from 15.47 to 2.91J/cm2 as Fe concentration content increases from 0.12 %wt. to 0.16 %wt. The porosity present in the casting is predicted to contribute to the ductility decrease. In addition, the decreasing value of UTS is predicted due to grain growth and dendrites formation. It is recommended that the maximum allowable Fe concentration for car rims application is 0.12 %wt.